Internet Usage and Its Utilization for Outpatient Treatment among Older Adults in Indonesia: Evidence from the 2020 National Socioeconomic Survey - Rahardja, Mugia Bayu; Puspitasari, Mardiana Dwi; Surbakti, Indra Murty (Althea Medical Journal, 2024)
Background: Health insurance is essential for older adults to get healthcare services. Interestingly, only around half of older adults in Indonesia had used the health insurance for outpatient care. Recently, internet usage has increased and is considered a predisposing factor for seeking therapy. This study aimed to explore the internet use among older adults for outpatient therapy.Methods: The National Socioeconomic Survey (SUSENAS)-core 2020 had included 29,905 older adults who had poor self-rated health and were unable to work or carried out other daily activities. Regression analysis was performed to determine the factors that influence the outpatient treatment.Results: Outpatient treatment utilization was highly associated with all predisposing factors such as age, gender, marital status, and education (p<0.05). Older adults who did not use the internet were 1.4 times more likely not obtain outpatient care (OR 1.362; 95% CI (1.207–1.537)). Those without health insurance had a higher probability of not seeking outpatient care (OR 1.643; 95% CI (1.551–1.741)) than those who had health insurance. Enabling factors, such as household wealth and living arrangements, were significantly associated with outpatient treatment utilization (p<0.05).Conclusions: Although health insurance remains the most significant factor, internet use is emerging as a way to increase coverage of outpatient treatment for the older adults.